Teoria da transição florestal: uma revisão bibliográfica para os biomas brasileiros - Schelp, Leonardo Kaiuá (Universidade Federal de São Carlos, 2023)
Brazil has a large territorial dimension, as well as an extensive biodiversity of both fauna and flora, and such magnitude is categorized into six biomes that have their characteristics and individualities. Furthermore, it is a country with large areas of vegetation cover, some unique and endemic, which are afflicted by extractivism and deforestation for the creation of arable fields and pastures, in addition to the demand for the ecossistemic resources themselves. The Forest Transition Theory (FTT) has been used to identify and categorize the mechanisms and stages of native vegetation in different countries and regions of the globe. However, there are few studies on the subject for the brazilian case, and even less, texts available in portuguese. Thus, foreign and national references were used to explore the variation in vegetation cover in each of the six brazilian biomes (Amazon, Cerrado, Caatinga, Atlantic Forest, Pampa and Pantanal) and try to identify the possibility of a forest transition. The references used range from motivations for deforestation in the colonial era to contemporary times in 2023. Thus, it is notable that brazilian biomes are in different stages of deforestation and conservation, in addition to having different mechanisms that enable forest transition, but with the participation of public policies as a common thread. In conclusion, there is still a lot of room for the topic in the brazilian case, since the studies are mostly focused in the Amazon and the Atlantic Forest, to the detriment of the other aforementioned biomes.
Forest transition theory: a literature review for Brazilian biomes
Keywords: Teoria da Transição Florestal; Brasil; Cobertura Vegetal Nativa; Forest Transition Theory; Brazil; Native vegetation cover; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA DOS RECURSOS NATURAIS